Upaya Meningkatkan Keberhasilan Pendidikan Agama Islam melalui Kegiatan Ekstra Kurikuler Berbasis Kurikulum Merdeka - Mollah, Moch. Kalam (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2024)
The integration of extracurricular activities within the framework of the Merdeka Curriculum has shown potential in enhancing students' comprehension and application of Islamic religious education. Given the limitations in instructional hours and curriculum content, there is a pressing need to explore alternative educational strategies to bolster students' understanding and practice of Islamic teachings. This study aims to evaluate the effectiveness of extracurricular activities based on the Merdeka Curriculum in improving the success of Islamic religious education. Specifically, it seeks to identify the types of activities implemented, the supporting factors, and the challenges encountered during their execution.The research adopts a qualitative descriptive approach. Data were collected through observations, interviews, and documentation to gain an in-depth understanding of the implementation of religious-themed extracurricular activities. The study focuses on various activities, such as qiro'ah, shalawat, Islamic studies, communal Dzuhur prayers, Dhuha prayers, and Ramadan camps, which are incorporated into the Merdeka Curriculum framework. The findings indicate that these extracurricular activities significantly enhance students' religious knowledge, character formation, and reinforcement of religious values. Additionally, these activities contribute to students' ability to resist negative influences and to practice Islamic teachings in their daily lives. The study concludes that religious extracurricular activities based on the Merdeka Curriculum play a vital role in the success of Islamic religious education. To maximize the benefits, increased support from schools and parents is essential. This research highlights the importance of integrating well-structured extracurricular activities into the educational system to foster a holistic development of students in line with Islamic values